"Buy everything": the model consumer-citizen of Disney's Zootopia. Issue 4 (1st October 2020) - Fritz, Alice Marianne
ABSTRACT: Given its history and status as a purveyor of quality children's entertainment, Disney's animated films are often associated with notions of "wholesomeness" and "family fun" by audiences. Consequently, consumption of Disney's media products tends to be an uncritical process. While a preferred decoding of Zootopia recognizes in its characters and story an affirmation of racial diversity and girl power, the film's polysemy conveys other latent messages that emerge through a negotiated reading. This paper focuses on the discourses within Zootopia that promote neoliberal values such as consumerism, individualism, and "small government." An analysis of the text reveals that Zootopia constructs an ideal citizen who obeys the law, performs their consumptive duties, believes in the capitalist myth of the American Dream, and happily accepts simulacra as substitute for reality. Furthermore, this paper makes the argument that Zootopia functions as a feature-length advertisement, not only for consumer products per se, but in a broader sense, for the consumerist lifestyle.